Factors Influencing Students’ Dropout in Bachelor’s Program in Kalika Multiple Campus, Pokhara - Subedi, Lok Nath (Kalika Journal of Multidisciplinary Studies, 2023)
Students’ dropout is one of the major phenomenons in higher education. This article primarily aimed to explore the factors influencing students’ dropout in the bachelor program of Kalika Multiple Campus, Pokhara and identify the reasons behind it. A descriptive design had been taken to describe the dropout rate and fifteen dropout students of bachelor’s degree faculty of education were selected as the respondents through judgmental purposive sampling procedure. Unstructured telephone interviewing was used as the tool for collecting the required information. This study bases on the theoretical tenets of Maslow’s Hierarchy of Needs, Motivation and Engagement, and Cognitive Load Theory. This study found that the main reasons of students’ dropout explored from student-related indicators were their low academic achievement in examination and irregularity in class; campus-related indicators were lack of academic support, feedback, motivation and encouragement from teachers, and problem of institutional information system; and lastly, family-related indicators were lacks of financial support from home and, different family problems. The implication of this study is to solve the problem of students’ drop out specifically in Kalika Multiple Campus and generally in the development of higher education programs in Nepal.